2015
DOI: 10.4103/1947-2714.168673
|View full text |Cite
|
Sign up to set email alerts
|

Cytokeratin 8 in association with sdLDL and ELISA development

Abstract: Background:Cardiovascular disease (CVD) remains the leading cause of morbidity and mortality worldwide. Cytokeratins (CKs) which may also be expressed in vascular smooth muscle cells (SMCs) are generally considered to be markers for the differentiation of epithelial cells. Small, dense, low-density lipoprotein (sdLDL) particles, also termed LDL-IV, independently predict risk of CVD.Aims:The aims of this study were to develop an analytical method, apart from ultracentrifugation capable of isolating sdLDL in ord… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…The lack of increase in PD-1 mRNA expression by Keratin 8-stimulated PBMCs from CAD patients suggests an aberration of normal tolerance pathways to the self-antigen. Aberrant self-reactive immune responses to Keratin 8 in the context of CAD needs further investigation but its potential involvement is supported by the report that Keratin 8 binds to small dense, low-density lipoprotein (sdLDL) [70]. Analysis of over 11,000 subjects in the Atherosclerosis Risk in Communitites (ARIC) study showed that sdLDL concentration predicted risk for coronary heart disease [71].…”
Section: Discussionmentioning
confidence: 99%
“…The lack of increase in PD-1 mRNA expression by Keratin 8-stimulated PBMCs from CAD patients suggests an aberration of normal tolerance pathways to the self-antigen. Aberrant self-reactive immune responses to Keratin 8 in the context of CAD needs further investigation but its potential involvement is supported by the report that Keratin 8 binds to small dense, low-density lipoprotein (sdLDL) [70]. Analysis of over 11,000 subjects in the Atherosclerosis Risk in Communitites (ARIC) study showed that sdLDL concentration predicted risk for coronary heart disease [71].…”
Section: Discussionmentioning
confidence: 99%